Contextual and Experiential Understandings of Privilege as Intersectional. (February 2023) - Lo, Kevin D.
With ongoing racial tensions, terms such as antiracism and diversity, equity, inclusion (DEI) are buzzwords on campuses across the United States. Yet resources, especially in management education, to teach privilege and intersectionality are limited. This article introduces four reflection exercises I have found valuable in facilitating students' different understandings (contextual and experiential) of privilege as intersectional. In addition, I present a conceptual framework for thinking about the intersection of multiple identities simultaneously given contextual and experiential understandings of privilege. In this way, this article makes both pedagogical and theoretical contributions. The sharing of these exercises, personal reflections, and teaching suggestions are geared at stimulating dialogue for how we learn and teach privilege, intersectionality, diversity, and antiracism. Instructors, regardless of their backgrounds, are invited to reflect on their intersectionality and privilege and also to consider integrating these exercises into their own DEI teaching.